1998
DOI: 10.1111/j.1365-2621.1998.tb15763.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Chloride Added to Irrigation Water of Mushrooms (Agaricus Bisporus) Reduces Postharvest Browning

Abstract: The influence of 0.3% CaCl 2 added to irrigation water on mushroom tyrosinase activity and postharvest browning was examined. Calcium concentration of mushrooms was significantly increased with the addition CaCl 2 to irrigation water but had no effect on inherent tyrosinase activity but reduced postharvest browning. The CaCl 2 had even more pronounced improvement in shelf life as indicated by reduced browning following a standard bruising treatment. Transmission electron micrographs indicate that increased lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Therefore the protein gels made with this recovered protein contained a higher calcium amount trapped in the gel matrix compared with gels made with protein recovered using NaOH as the processing base. The increased calcium may have inhibited the reaction between tyrosinase and its phenolic components, therefore decreasing browning . Moreover, calcium particles are white and water‐soluble.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore the protein gels made with this recovered protein contained a higher calcium amount trapped in the gel matrix compared with gels made with protein recovered using NaOH as the processing base. The increased calcium may have inhibited the reaction between tyrosinase and its phenolic components, therefore decreasing browning . Moreover, calcium particles are white and water‐soluble.…”
Section: Resultsmentioning
confidence: 99%
“…This improvement in whiteness has been attributed to increased stability of vacuole membranes and slow enzymatic browning reactions accomplished by the prevention of tyrosinase mixing with its substrate. 5 Earlier studies also reported the bene®cial effect of CaCl 2 irrigation on the postharvest colour of mushrooms. 16,18,25 To our knowledge, few reports have attempted to trace the in¯uence of CaCl 2 irrigation on at-and postharvest texture through application of a wide range of dosages.…”
Section: 18mentioning
confidence: 93%
“…16±18 The most notable improvement in storage and shelf-life is reduced mushroom browning, which has recently been attributed to increased vacuolar membrane integrity. 5 However, relatively little is known about the effect of CaCl 2 on mushroom number and size mix (percententages of small and large fruit bodies) within a¯ush and their distribution among¯ushes. Other issues of interest include the identi®cation and study of factors responsible for at-and post-harvest ®rmness following CaCl 2 irrigation, 19,20 since experimental applications of a wide range of CaCl 2 concentrations are scarce and limited to rates lower than 0.55%.…”
Section: ±10mentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium ions have also been reported to decrease firmness loss in fresh‐cut pears (Sapers and Miller 1998), fresh‐cut mangosteens (Manurakchinakorn et al. 2005) shredded carrots (Izumi and Watada 1994), mushrooms (Kukura et al. 1998) and peaches (Manganaris et al.…”
Section: Resultsmentioning
confidence: 99%